Economic, Social and Cultural Factors Associated with the Adoption of Firewood- Burning Improved Cook stoves – Case of the district of Chiguata, province and department of Arequipa in Peru - Moreno Morales, Ana Isabel (2016)
The purpose of this research was analysing the economic, social and cultural factors associated with the adoption of firewood-burning improved cook stoves in users of the district of Chiguata, province and department of Arequipa in Peru. This is a bivariate exploratory prospective observational and analytical study. Probabilistic dependencies between associated variables were obtained through non-parametric tests with Pearson Chi- square test; and the parametric tests were obtained with the Kolmogorov-Smirnov test and the Student's t-test for p-value > 0.05.The variables associated with the adoption are: knowledge of use, maintenance and repair of the cook stove; investment in improving their kitchen; dissemination of educational messages on the benefits of the improved cook stove; efects of indoor air pollution, specially broadcasted by local radios; perception of the risk on the exposure to polluting fumes; having safe water; perceiving the improved cook stove as the safest technology against burns; and use of liquefied petroleum gas (LGP). The age, number of children, family income, animal breeding, profession and/or educational level are not associated with the adoption.